2021
DOI: 10.1155/2021/6696857
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease and Cardiovascular Diseases: The Heart of the Matter

Abstract: Nonalcoholic fatty liver disease (NAFLD) has emerged as the most frequent cause of liver disease worldwide, comprising a plethora of conditions, ranging from steatosis to end-stage liver disease. Cardiovascular disease (CVD) has been associated with NAFLD and CVD-related events represent the main cause of death in patients with NAFLD, surpassing liver-related mortality. This association is not surprising as NAFLD has been considered a part of the metabolic syndrome and has been related to numerous CVD risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 109 publications
0
28
0
5
Order By: Relevance
“…The main cause of death in NAFLD individuals is cardiovascular diseases (CVDs) [ 71 ]. One reason for developing CVDs is atherogenic dyslipidemia, which is characterized by a low HDL-C concentration and high LDL-C, TC, and TG concentrations [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main cause of death in NAFLD individuals is cardiovascular diseases (CVDs) [ 71 ]. One reason for developing CVDs is atherogenic dyslipidemia, which is characterized by a low HDL-C concentration and high LDL-C, TC, and TG concentrations [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of death in NAFLD individuals is cardiovascular diseases (CVDs) [ 71 ]. One reason for developing CVDs is atherogenic dyslipidemia, which is characterized by a low HDL-C concentration and high LDL-C, TC, and TG concentrations [ 71 ]. Our analysis with five studies showed that HDL-C did not change after exercise, which is consistent with another SR. LDL-C was significantly decreased after exercise, but no changes were observed in aerobic exercise alone.…”
Section: Discussionmentioning
confidence: 99%
“…In another cohort study with a very long follow-up (33 years), advanced histological NAFLD fibrosis stages were predictors of all-cause and disease-specific mortality, including CVD, while inflammatory activity grade was not associated with mortality risk [ 31 ]. The pathophysiological mechanisms behind the association of liver fibrosis in NAFLD with cardiovascular disease are still incompletely understood and may involve other pathways besides insulin resistance, such as oxidative stress, inflammation, and gut microbiota [ 32 ]. Another possible physiopathological link between advanced liver fibrosis and atherosclerotic disease development in diabetes was the finding that individuals with NAFLD and diabetes who increased or persisted with abnormally high aortic stiffness during follow-up were also at particular risk of having advanced liver fibrosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is produced to protect against excessive immune response, limits organ damage, in particular, plays a protective role in liver fibrogenesis and prevents the progression of hepatic steatosis. [11][12][13]. In the liver, IL-10 was detected in hepatocytes, stellate cells, and Kupffer cells, but only a few studies have been performed to investigate the role of endogenous IL-10 in the progression of NAFLD [14].…”
Section: Medicine and Dentistrymentioning
confidence: 99%